2018
DOI: 10.1088/1742-6596/994/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the geometry on magnetic interactions in a retina fixator based on a magnetoactive elastomer seal

Abstract: Abstract.We study the effects the geometric configuration has on magnetic interactions between a magnetoactive elastomer (MAE) sample and various systems of permanent magnets for problems with both flat and curved geometry. MAEs consist of a silicone polymer matrix and iron filler microparticles embedded in it. Permanent magnets are cylindrical neodymium magnets arranged in a line on a flat or curved solid surfaces. We use computer simulations, namely the finite element method, in order to study the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Furthermore, the pressure is lower in the curved configuration in comparison with the flat one as it has been predicted theoretically in Ref. . Indeed, when the system is bent the direction of the interaction force changes.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, the pressure is lower in the curved configuration in comparison with the flat one as it has been predicted theoretically in Ref. . Indeed, when the system is bent the direction of the interaction force changes.…”
Section: Resultssupporting
confidence: 73%
“…The results on the flat geometry were promising but theoretical calculations performed in Ref. for curved configurations corresponding to real human eyes have revealed that the surface curvature introduces sensitive corrections into the average pressure realized in the magnetic system. The difference in pressures for flat and curved cases can reach 20% at the distance of 0.7 mm between the nearest faces of the magnetic components of the retina fixator; the value 0.7 mm corresponds to the average thickness of the human sclera together with retina and choroid .…”
Section: Introductionmentioning
confidence: 97%
“…Hence, upon introducing the generalized effective susceptibility χ A eff in Equation ( 29) and passing over to Equation (30) this self-demagnetization is implicitly, and exactly, taken into account. Furthermore, by definition, see Equation (29), the components of χ A eff are bound to moderate values even though the components of the generalized susceptibility itself, χ A = ∇ A L(A), may become very large. In contrast to Equation (26), it is now χ A eff which is forming the prefactor in Equation ( 30), resp.…”
Section: The Local Magnetization Within An Individual Particlementioning
confidence: 99%
“…Nevertheless, we also note a fundamental drawback for magnetization functions L(•) beyond the 'true' linear magnetization scheme. Only in this case where M = χH, or general M = χ • H, the here defined χ A , Equation (28), and accordingly also the effective χ A eff , Equation (29), are pure material parameters. They simply become χ A = χ, resp.…”
Section: The Local Magnetization Within An Individual Particlementioning
confidence: 99%
See 1 more Smart Citation